The Influence of Audit Quality on Financial and Non-Financial Performance: Evidence from Iraqi Industrial Corporations - AL Kaabi, Amel Fadhil Akho Bashah; Wahhab, Asaad (Technium Social Sciences Journal, 2025)
In a continually changing business environment, the integration of audit quality and financial performance of industrial firms is critical to a company's success and continuity, and audit quality complements this relationship. As a result, the current study aims to quantify the impact of audit quality on financial performance, while also examining the relationship between audit quality and financial performance, as well as its effect on non-financial performance in Iraqi industrial companies. This assignment aims to improve the overall performance of Iraqi industrial enterprises and promote sustainability. A questionnaire of 60 paragraphs was created for this purpose, with equal distribution across the three categories (audit quality, financial performance, and non-financial performance). The study population consisted of internal auditors and accountants from 29 public industrial companies and 21 private joint-stock industrial companies. The questionnaire was distributed to a random sample of them, resulting in 154 responses. Demographic data were analysed utilizing descriptive statistics, and hypotheses were tested using both simple and multiple linear regression analyses. Statistical study revealed a link between audit quality and financial performance. Financial performance was 27.6%, a low percentage, but the association between audit quality and non-financial success was 49.4%. The findings also indicate that the auditor's industry experience and awareness of the importance of achieving quality have a substantial impact on audit performance. Furthermore, the existence of key performance indicators (KPIs) connected to strategic objectives improves the financial performance of industrial organizations. Transparency in environmental, social, and governance reports influences investment and funding decisions.